Cytotoxicity of thymoquinone and thymoquinone-loaded nanostrustured lipid carrier on cervical cancer cells (SiHa and HeLa) - Ng, Wei Keat (2015)
Cancer is a life-threatening disease and a major leading cause of death worldwide. Drug resistance and adverse effects impede the success of chemotherapy. Hence, searching for anti-cancer bioactive compounds with low toxicity from natural products is now in demand. Thymoquinone (TQ), the bioactive compound of Nigella sativa, has been reported to exert anti-cancer properties. Nevertheless, TQ exhibits poor oral bioavailability. Therefore, nanostructured lipid carrier (NLC), provides an alternative delivery system for TQ to overcome the limitations. The objective of the study was to determine the cytotoxicity and mechanisms of action of TQ and TQ-NLC towards cervical cancer cells (SiHa and HeLa). The cytotoxicity of TQ towards SiHa and HeLa was determined by MTT assay. Cell cycle and mode of cell death was performed by using flowcytometry. The expression of p53, Bcl-2 and Bax, and caspases was studied by using Western blot and ELISA, respectively. Thymoquinone-loaded nanostructured lipid carrier (TQ-NLC) was synthesized by high pressure homogenization method. Physicochemical characteristics of TQ-NLC were determined. Cytotoxicity of TQNLC_ 4 towards SiHa and HeLa cells was evaluated by MTT assay. In vitro drug release kinetic, gastrointestinal digestion, absorption and bioavailability studies of TQ-NLC_4 were performed. Result shows that TQ was cytotoxic towards SiHa and HeLa cells by inducing cell cycle arrest and apoptosis in the cells. Elevation of Bax to Bcl-2 ratio and expression of caspase-3 and -9 were noted in SiHa cells while in HeLa cells, elevation of Bax to Bcl-2 ratio and expression of caspase-3, -8 and -9 were noted. Physicochemical analysis revealed that average diameter of TQ-NLC_4 was less than 100 nm. TQ-NLC_4 was found stable up to 24 months. High EE and DLC of TQ-NLC_4 were achieved. TQNLC_ 4 was cytotoxic towards SiHa and HeLa cells. TQ was released from NLC in a zero-order manner. Degradation and aggregation of TQ-NLC_4 occurred in simulated intestinal fluid. In vitro absorption and bioavailability studies indicated that bioavailabilty of TQ-NLC_4 was high. In conclusion, TQ was cytotoxic against the cervical cancer cells by modulating the apoptotic pathways. NLC conferred drug controlled release, protection and enhanced bioavailability to TQ. Hence, TQ-NLC_4 may be a promising anti-cancer agent against cervical cancer.